Wound Coverage in Extensive Necrotizing Fasciitis with Chronic Liver Disease - M. Choundappan (Indian Journal of Plastic Surgery)
Chronic liver disease is characterized by lowered immunity, altered hematological parameters, and poor wound healing. Surgeons may hesitate to intervene in such patients when they present with necrotizing fasciitis (NF) or misinform the patients regarding their chances of survival. This is because of the poor nutritional state, thrombocytopaenia, and abnormal coagulation profile. However, recent guidelines show that platelet count and prothrombin time/international normalized ratio (PT-INR) do not predict postoperative bleeding. We can proceed with debridement followed by skin grafting of wounds in such patients. This will help reduce the high mortality rate of NF in cirrhotic patients.